Peran Penyuluh Pertanian Terhadap Adopsi Permanan Teknologi Alat dan Mesin Pertanian oleh Petani di Kecamatan Cempaka Kota Banjarbaru - Iis Kasumi; Luthfi Fatah; Mariani Mariani (Universitas Lambung Mangkurat, 2013)
The existence of technology has made the fife much easier, and now the technology is inseparable on human fife. By using the appropriate technology in each farming process , the time and labor can be reduced significantly. The study is aimed to explore the potency of farm machinery adoption, the role of extension officer on the adoption process, and co identify the problem faced by the officer on the adoption process. The study was conducted in Kecamatan Cempaka, Kota Banjarbaru, involving 40 rice growers as respondents. The study show that the potency level of adoption is high as the score is 90.82%. However, the role of extension officer is low (score 63.92%). This is because of low supervision, less controlling , and less evaluation on the adoption process.